ENERGY PROBLEM AND ENVIRONMENT: ऊर्जा समस्या एवं पर्यावरण - Pathak, Sunita (International Journal of Research -GRANTHAALAYAH, 2015)
Energy is a very important infrastructure / infrastructure / point of view of economic development. Energy plays a major role in the ecological balance of nature, which maintains the interaction between biological and abiotic components of the natural environment. By considering development as mere economic and material development, human beings get involved in indiscriminate exploitation of natural resources by inventing fast-paced technology to compensate for the goal. This is where he makes an error and he starts destroying the environment at the point of development, which leads to many social problems, one of which is energy crisis. The modern era of human history began with the modern technology of production and the demand for energy went on increasing, in the last three or four thousand years, the human society could not use in the last three or four thousand years, many times more modern society used it in only 100 years Due to which the pressure on the sources of limited reserves is increasing, which is the main reason for the energy crisis. Due to not concentrating on non-conventional sources of energy in a timely manner, it is increasing further, so we have to pay special attention to non-conventional sources like solar energy, wind energy, etc. soon. आर्थिक विकास केेेेेेेेेेेेेेेेेे दृ्रष्टिकोण से ऊर्जा एक अत्यन्त महत्वपूर्ण अवस्थापना/इन्फ्रास्ट्रक्चर/ है। प्रकृति के पारिस्थितिक संतुलन में ऊर्जा की मुख्य भूमिका रहती है, जो प्राकृतिक परिवेश के जैविक तथा अजैविक घटकों के मध्य अन्तःक्रिया बनाए रखती है। मनुष्य विकास को मात्र आर्थिक एवं भौतिक विकास मानकर लक्ष्य की प्रतिपूर्ति के लिए तीव्र गति वाली तकनीक का आविष्कार कर प्राकृतिक संसाधनो के अंधाध्ंाुध विदोहन मे जुट जाता है। यहीं उससे त्रुटि हो जाती है और वह विकास के स्षान पर पर्यावरण का विनाश करने लगता है, जिससे अनेक सामाजिक समस्याओं को जन्म होता है, जिसमें से एक है ऊर्जा संकट । उत्पादन की आघुनिक तकनिक के साष मानव इतिहास का आधुनिक युग शुरू हुआ एवं ऊर्जा की मांॅंग बढ़ती चली गई, जितनी ऊर्जा का उपयोग विगत तीन या चार हजार वर्षो में मानव समुदाय नहीं कर पाया था, उससे कई गुना आध्ुनिक समाज ने केवल 100 वर्षो में किया है जिससे सीमित भंडार वाले स्त्रोतों पर दबाव बढ़ता चला जा रहा है जो ऊर्जा संकट का मुख्य कारण है । ऊर्जा के गैर परम्परागत स्त्रोतों पर समय पर घ्यान नहीं देने के कारण यह और बढ़ता जा रहा है अतः हमें शीध्र्र ही गैर परम्परागत स्त्रोत जैसे सौर ऊर्जा, पवन ऊर्जा आदि पर विशेष घ्यान देना होगा ।